Evaluating point and density forecasts of DSGE models - Maik Hendrik Wolters (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2012)
This paper investigates the accuracy of point and density forecasts of four DSGE models for inflation, output growth and the federal funds rate. Model parameters are estimated and forecasts are derived successively from historical U.S. data vintages synchronized with the Fed's Greenbook projections. Point forecasts of some models are of similar accuracy as the forecasts of nonstructural large dataset methods. Despite their common underlying New Keynesian modeling philosophy, forecasts of different DSGE models turn out to be quite distinct. Weighted forecasts are more precise than forecasts from individual models. The accuracy of a simple average of DSGE model forecasts is comparable to Greenbook projections for medium term horizons. Comparing density forecasts of DSGE models with the actual distribution of observations shows that the models overestimate uncertainty around point forecasts.
urn:nbn:de:hebis:30:3-268720
Keywords: C53; E31; E32; E37; 330; DSGE models; forecasting; model uncertainty; forecast combination; density forecasts; real-time data; Greenbook